Ecosystems and History of Evolution and Spread of Sugar Producing Plants in the World-an Overview - Prasad, Rajendra; Singh , Yashbir (International Journal of Bio-resource and Stress Management, 2020)
Plants used for making sugar differ from ecosystem to ecosystem of the world and history has played a great role in their spread. People in the tropics and sub-tropics (Papua New Guinea, China, and India) were the first to domesticate sugarcane, numerous sugars producing plant in the world. ICAR–Sugarcane Breeding Institute, Coimbatore in India was the first to do the breeding work in sugarcane and the Coimbatore canes or varieties developed from them dominate the sugarcane producing areas in the world. Indians first made jaggery (Gur) by concentrating the juice by boiling it and cooling it in earthen pots. They were also the first to develop crystal white sugar producing technology in the beginning centuries of CE. Of course, it was later improved by the British, who dominated the European sugar market. Europeans, specially Poles, Germans and French domesticated sugar beet and developed technology for making sugar from it. Aboriginal in North America were the first to develop the technology for making sweet syrup from maple tree and the migrants from Europe then further improved it. Canada is the world’s leading country in exporting maple syrup today. People in the southern states of US developed sweet sorghum for making sorghum syrup. Corn producers in USA developed the technology for making corn syrup.